CASUISTRY OF DISEASES IN DONKEYS AND MULES ATTENDED AT THE VETERINARY HOSPITAL IN THE COUNTRYSIDE OF SÃO PAULO, BRAZIL - Costa, Thayssa Duarte; Ferreira, Karen Nayara Abdala; Anobi, Bruna Tambeli; Souza, Camilla de; Segura, Julio Guerra (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
This study aimed to conduct an analysis of the main diseases in donkeys and mules attended at the Veterinary Hospital of Centro Universitário Anhanguera in Leme, São Paulo, Brazil, from 2009 to 2019. Through a review of clinical cases derived from the hospital records and data tabulation, the most common diseases affecting these species were identified and studied, providing relevant information on these conditions. The study collected a total of 66 records, with 30,30% referring to donkeys and 69,70% to mules. Among the donkeys, 100% of the studied cases were males under 15 years old, while the female mules had significant numbers compared to the donkeys (63,04% versus 36,96% of males), between 5 and 10 years of age. Regarding the diseases found across all studied species, the three highest concentrations were records related to gastroenteric problems (40,90%), followed by dermatological diseases (24,25%) and musculoskeletal problems (18,19%). It was concluded that more effective and targeted management of these species, along with specialized and periodic veterinary care, as well as increased awareness among owners regarding proper care, contribute to the health and well-being of donkeys and mules.